Low-temperature chemical looping oxidation of hydrogen for space heating - Güleç, Fatih; Okolie, Jude A.; Clough, Peter T.; Erdogan, Ahmet; Meredith, Will; Snape, Colin E. (Elsevier, 2023)
Chemical looping combustion (CLC) is an advanced combustion process in which the combustion reaction splits into two parts; in the first reaction metal oxides are used as oxygen suppliers for fuel combustion and then in the second reaction, reduced metal oxides are re-oxidised in an air reactor. Although this technology could be applicable for the safe implication of “low-temperature oxidation of hydrogen”, there is limited understanding of oxygen carrier reduction stages and the oxidation mechanism of hydrogen throughout the process. The novelty of this research lies in its pioneering investigation of low-temperature oxidation of hydrogen through chemical looping technology as a safe and alternative heating system, using three distinct metal oxide oxygen carriers: CuO, Co3O4, and Mn2O3. The oxidation of hydrogen over these oxygen carriers was comprehensively studied in a fixed-bed reactor operating at 200–450 °C. XRD analysis demonstrates that CuO directly reduced to metallic Cu at 200–450 °C, instead of following a sequential reduction step CuO→Cu4O3→Cu2O→Cu throughout the temperature. Co3O4 was reduced to a mixture CoO and Co at 450 °C, which may refer to a sequential reduction step Co3O4→CoO→Co with increasing the temperature. Decreasing the reduction temperature led to an elevation in CoO formation. Mn2O3 can also reduce to a mixture of Mn3O4 and MnO at temperatures between 250 and 400 °C. Compared to temperature, the increase in the residence time did not show any further reduction in Mn2O3. SEM results showed that most of the metal oxide particles were evenly dispersed on the supports. Based on the experimental results, a potential reduction stage of CuO, Co3O4 and Mn2O3 was proposed for low-temperature hydrogen oxidation, which could be a potential application for space heating using safe hydrogen combustion.
Keywords: Advanced combustion; Chemical looping combustion (CLC); Hydrogen; Oxygen carriers